Bacteremic Pneumococcal Pneumonia: a Longitudinal Study in 279 Adult Patients from a Single Center - Gentile, Jorge (2018)
Background: Bacteremic pneumococcal pneumonia (BPP) is the most common clinical presentation of invasive pneumococcal disease (IPD). Although it has been extensively studied, there is little knowledge in our region in relation to burden of disease, demographic and outcome features.Methods: We conducted a prospective, longitudinal, observational study from 1989 to 2015 in adult patients with BPP, in order to deepen our knowledge of the characteristics of this disease in our community hospital in Tandil, Argentina.Results: 279 patients were included. The mean incidence was 2.8/1000 admissions with a sharp decrease in the last two years, reaching 0.8/1000 admissions. Mean patient age was 60 years. Comorbidities were found in 65% of the cases. Non-respiratory symptoms occurred in 50% of cases.Infiltrates on chest x ray were predominantly unilateral (75%) and lobar (57%). Regarding severity, a low PSI score I-II-II was found in 178 patients (64%), 60 (22%) were admitted to ICU, 40 (14%) required mechanical ventilation, and 21 (8%) developed empyema. Penicillin resistance was not found. Mortality was 18% (49/279), and by a multivariate analysis it was associated with confusion(OR= 5.44), age>80 years (OR =5.72), leukopenia (OR =5.73) and dyspnea (OR=7.87).Conclusions: In this study of 279 bacteremic pneumococcal pneumonia we reinforce previous knowledge on this disease regarding incidence and clinical features and confirm a considerable an early mortality associated to age and severity of disease at onset. Recent changes in incidence of BPP in adults could be secondary to herd effect of PVC 13 a vaccine that is mandatory in children in our community since 2012.